Appraisal of Socio-economic, Infrastructural and Environmental Impacts of Flood in Makurdi Local Government Ares of Benue State, Nigeria - Ikyapa, Tertese Peter; Abdulhamid, Adnan; Rilwanu, Tasi’u Yalwa; Daura, Mala Muhammed; Alogo, Philip Aondosoor (Journal of Sustainability and Environmental Management, 2022)
Among the common natural hazards experienced in the world today, flood is said to be the most devastating in terms of the area covered and frequency of occurrence. Floods cause serious damage to lives and properties, disrupt economic activities, and, in turn, threaten the sustainable development of human settlements. In Nigeria, flooding has become a recurring phenomenon, sometimes with devastating effects. This study was aimed at assessing the socio-economic, infrastructural, and environmental impacts of floods in Makurdi Local Government Area (LGA). A non-probability sampling technique involving the use of a well-structured questionnaire was adopted in obtaining the required information. Purposive random sampling was used to select four hundred (400) flood victims from the nine (9) local wards bordering the Benue River. Analysis was done using Microsoft Excel and the findings were presented in tables and charts using percentages. The result showed that floods have a huge impact on the community, with greater damage 44% recorded on socio-economic activities (farming, marketing, and administration), followed by a 32% impact on infrastructural facilities (roads, hospitals, and schools), and a relatively lower impact 24% recorded on environmental variables (water, land, and vegetation). An Analysis of Variance (ANOVA) test conducted on these revealed that there is a significant variation in the impact created by floods on the study variables. Flood mitigation and preparedness plans were found to be the leading challenges to long-term flood disaster management in the area. The paper calls for collaborative efforts from residents, flood disaster management agencies, or stakeholders to reduce the impact and improve decisions towards ameliorating the menace of floods in the area. The evidence in this paper seeks to promote actions toward combating flooding and improving flood disaster management in Nigeria.